Macro world in nano hands: Nano revolutions in medicine and food processing with the aid of nanosensors - Gayatri Kotekar; Sucheta Gaikwad; Anukriti Nigam (Sensors International)
Nanotechnology, the manipulation of materials at the nanoscale, has emerged as a transformative force with profound implications for diverse fields. This following review explores the versatile administration of nanotechnology in both the biomedical and food processing disciplines, highlighting the potential breakthroughs and advancements achieved in these critical domains. Nanotechnology has made significant advancements in drug delivery, imaging, and diagnostics possible in the biomedical field. Particular characteristics of nanoscale materials, like nanoparticles and nanocarriers, improve their compatibility with biological systems. As a result, targeted drug delivery systems have been created, enabling precise drug administration and fewer side effects. Furthermore, improved diagnostic capabilities are made possible by nanoscale imaging agents, which allow for early disease detection. Additionally, the development of nanosensors for the real-time tracking of physiological variables has been made possible by nanotechnology, which has aided in the rise of personalized medicine. Nanotechnology has completely changed a number of aspects of the food processing industry, including packaging, preservation, and food safety. Antimicrobial nanomaterials have been used to put an end to the growth of harmful microorganisms, thus increasing food safety. Additionally, food packaging using nanocomposites has shown to have enhanced barrier qualities, extending the shelf life of perishable items and cutting down on food waste. The creation of intelligent packaging systems that can continuously check the freshness of food is made possible by nanoscale materials. The use of nanotechnology in these fields presents ethical and safety issues, despite its enormous potential. In order to ensure the responsible integration of nanotechnology into biomedical and food processing practices, ongoing research is devoted to addressing these challenges. The ongoing investigation of nanotechnology's potential in these fields offers hope for the development of safer, more effective, and technologically sophisticated solutions that will improve human health and welfare.